Pengaruh GCG, DPK, NPF, dan Ukuran Bank terhadap Kinerja Bank Umum Syariah - Alfi, Rini Nur; Irsyad, Mohamad (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
Islamic banking has existed in Indonesia since 1992, the increasing development of Islamic bank can be seen from the bank’s performance, namely profitability, which is measured using Return On Equity (ROE). ROE shows that the development of Islamic bank fluctuated from 2019 – 2023. This study was conducted to analyze the effect of the implementation of Good Corporate Governance (GCG),third party funds (DPK), non-performing financing (NPF), and bank size on the performance of commercial banks as measured by by return on equity (ROE). This study uses a quantitative approach, with secondary data referring to 16 Islamic commercial banks registered with the Financial Services Authority (OJK) 2019-2023 Sampling was done using purposive sampling, with the criteria of Sharia Commercial Banks registered with the OJK in 2019 – 2023 and issuing annual reports and GCG reports from 2019 to 2023. Based on these criteria, 50 data from 10 Islamic commercial banks were obtained as a sample of this study. The method used was panel data regression with the Eviews 10 analysis tool.The results of this study indicate that the variable GCG and DPK do not have a significant effect on ROE, the NPF variable has a significant negative effect on ROE and the bank size variable does not effect on ROE. However, simultaneously the variables GCG, DPK, NPF, bank size has a Prob. value of 0,020234 < 0.05, has a significant effect on ROE.